2021
DOI: 10.3389/fneur.2021.621257
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Respiratory Accessory Muscles and Diaphragm Pillars MRI and Pulmonary Function Test in Late-Onset Pompe Disease Patients

Abstract: Objectives: Pompe disease is a rare genetic disease produced by mutations in the GAA gene leading to progressive skeletal and respiratory muscle weakness. T1-weighted magnetic resonance imaging is useful to identify fatty replacement in skeletal muscles of late-onset Pompe disease (LOPD) patients. Previous studies have shown that replacement by fat correlates with worse results of muscle function tests. Our aim was to investigate if fat replacement of muscles involved in the ventilation process correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In addition, diaphragmatic lipid accumulation was quantified by MRI with proton density fat fraction (MRI‐PDFF). We assessed the lipid content of the diaphragm by analyzing PDFF of the diaphragm pillars (Figure 1C), which are two musculotendinous structures surrounding the anterior lumbar spine [23]. Our data showed that PDFF of the diaphragm was significantly higher in people with obesity than in lean control individuals (cohort 3, n = 18; Figure 1D), indicating the lipid accumulation in the diaphragm of people with obesity.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, diaphragmatic lipid accumulation was quantified by MRI with proton density fat fraction (MRI‐PDFF). We assessed the lipid content of the diaphragm by analyzing PDFF of the diaphragm pillars (Figure 1C), which are two musculotendinous structures surrounding the anterior lumbar spine [23]. Our data showed that PDFF of the diaphragm was significantly higher in people with obesity than in lean control individuals (cohort 3, n = 18; Figure 1D), indicating the lipid accumulation in the diaphragm of people with obesity.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study revealed increased fall risk in patients with more severe involvement of trunk muscles ( 13 ). Trunk muscle involvement has also been found to correlate with negative respiratory outcomes and balance function in LOPD and DM1 ( 10 , 12 ). According to Vill et al, ultrasound could detect muscle abnormality in clinically affected muscles and demonstrated that clinical muscle strength was highly correlated with muscle abnormality in LOPD ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Poor trunk function may cause an increased falling risk, a decreased daily activity, and decreased upper and lower limb functional movements ( 11 ). In addition, the fat replacement of back, abdominal, and deep trunk muscles have been found to be correlated with poor respiratory function in LOPD ( 12 ). In recent studies, trunk impairment score (TIS) and trunk control test (TCT) have been used to assess static and dynamic trunk muscle function in patients with stroke ( 11 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies evaluated diaphragmatic motion with D-MRI in patients with idiopathic scoliosis and neuromuscular diseases [8][9][10][11]. The structure and motion of the diaphragm and chest wall also have been applied to assess health and some chronic respiratory diseases, such as chronic obstructive pulmonary disease (COPD) and asthma [12][13][14].…”
Section: Introductionmentioning
confidence: 99%